2021
DOI: 10.33545/gynae.2021.v5.i5a.1006
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year review of obstructed labour and its sequalae in the Federal Medical Centre, Yenagoa, South-South, Nigeria

Abstract: Background: Obstructed labour is associated with significant maternal and perinatal morbidity and mortality. Objective: To determine the incidence of obstructed labour and its maternal and perinatal outcomes. Materials and Methods: This retrospective survey was carried out between 1st January, 2016 and 31st December, 2020. Data were retrieved, entered into a pre-designed proforma, and analysed using IBM SPSS version 23.0. Results were presented in frequencies and percentages. Results: The case incidence of obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This study like the ones preceding it here was a tertiary hospital-based study in an urban area which could explain the lower value found. In south-southern Nigeria, the prevalence in a retrospective study was 1.1% [10]. This was another tertiary hospital-based study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This study like the ones preceding it here was a tertiary hospital-based study in an urban area which could explain the lower value found. In south-southern Nigeria, the prevalence in a retrospective study was 1.1% [10]. This was another tertiary hospital-based study.…”
Section: Discussionmentioning
confidence: 88%
“…A similar study in Abakalikki, south-east, Nigeria, over a 5-year period, found a prevalence of 3.4% [8] and women in their second and third decades of life were prominent, constituting 91.6% of all the cases. In another retrospective study in Nnewi, south-east Nigeria, a prevalence of 1.5% [9] of obstructed labour was found and in another retrospective study in Bayelsa, south-south, Nigeria, the incidence of obstructed labour was 1.1% and unbooked, nulliparous women featured prominently in the demographics of the women [10]. In Obafemi Awolowo University Teaching Hospital, Ile-Ife, south-west, Nigeria, the incidence of obstructed labour was 1.99% [11], in Usman Danfodio University Teaching Hospital Sokoto, north-west, Nigeria, it was 1.79% [12], in Gombe, north-east, Nigeria, it was 4.0% [13].…”
Section: Introductionmentioning
confidence: 99%